Mental Health Assessment of Minors in the Juvenile Justice System - Curtis Heaston; Michael Jenuwine; Diane N. Walsh; Gene Griffin (Washington University Journal of Law & Policy, 2003)
Recent reports recognize that children and adolescents with undiagnosed mental illnesses make up a significant proportion of youth in the juvenile justice system. In determining how to rehabilitate youth in the juvenile justice system, judges, lawyers, and probation officers are starting to look at mental health problems as one element contributing to delinquent behavior. It is becoming more common for attorneys to request “mental health assessments” for their juvenile clients. Problems arise, however, in determining what specifically constitutes such an assessment, and in deciding what to do with this information once it is obtained. In 2001, the Illinois Cook County Juvenile Court convened the interdisciplinary Juvenile Justice Committee on Mental Health Assessments to address this issue. Specifically, the committee attempted to define the components and protocol for mental health assessments, how to handle the results of such assessments, and, ultimately, what to do with the youth. The following summarizes the committee’s findings, and outlines its relevance to interdisciplinary clinical legal education.
Keywords: Juvenile delinquents; Mental health; Multidisciplinary practices; Clinical legal education; Administration of juvenile justice; Criminal rehabilitation; Mentally ill teenagers; Cook County; Illinois; Illinois; United States